2020
DOI: 10.1093/chemse/bjaa024
|View full text |Cite
|
Sign up to set email alerts
|

Orthonasal, but not Retronasal Olfaction Is Specifically Impaired in Parkinson’s Disease

Abstract: Olfactory dysfunction (OD) in Parkinson’s disease (PD) appears several years before the presence of motor disturbance. Olfactory testing has the potential to serve as a tool for early detection of PD, but OD is not specific to PD as it affects up to 20% of the general population. Olfaction includes an orthonasal and a retronasal components; in some forms of OD, retronasal olfactory function is preserved. We aimed to evaluate whether combined testing components allows for discriminating between PD-related OD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our results are in line with the notion of olfactory bulb volume to be a neuroanatomical correlate of olfactory function ( Buschhuter et al, 2008 , Hummel et al, 2015 ), independently of any underlying condition that may affect its volume. Interestingly, a recent study however suggests that overall chemosensory function such as flavor perception may be one method to behaviorally distinguish between PD and NPOD patients ( Aubry-Lafontaine et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with the notion of olfactory bulb volume to be a neuroanatomical correlate of olfactory function ( Buschhuter et al, 2008 , Hummel et al, 2015 ), independently of any underlying condition that may affect its volume. Interestingly, a recent study however suggests that overall chemosensory function such as flavor perception may be one method to behaviorally distinguish between PD and NPOD patients ( Aubry-Lafontaine et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an ideally olfactory battery to detect subclinical smell loss in PD should include olfactory identification and odor threshold. Interestingly, orthonasal and retronasal scores were not significantly correlated in PD patients and it was orthonasal not retronasal olfaction that was specifically impaired in PD patients (Ciofalo et al, 2006;Aubry-Lafontaine et al, 2020). This evidence indicates that the retronasal olfactory system was relatively unimpaired and the decrease in flavor perception is less pronounced in PD patients than what one would expect from the degree of orthonasal olfactory impairment.…”
Section: Olfactory Dysfunction Associated With Neurodegenerative Disementioning
confidence: 99%
“…One possibility may be retro-nasal testing, i.e., the perception of olfactory stimuli in the oral cavity perceived via the nasopharynx. This main contributor to flavor perception appears to be distinctly affected in PD [73]. Another method is to combine olfactory testing with other chemosensory tests.…”
Section: Opportunities Of Od As Early Marker In Pdmentioning
confidence: 99%
“…In fact, olfactory testing enables the identification of iRBD patients at short-term risk of developing DLB or PD [66]. However, one cannot yet distinguish the phenoconversion trajectory with smell tests alone, even if, after phenoconversion, DLB patients and PD patients seem to be distinguishable using olfactory and trigeminal threshold test [73,74]. The combined study of the olfactory and trigeminal systems appears to be a promising avenue, albeit this remains speculative.…”
Section: Pitfalls Of Od As Early Marker In Pdmentioning
confidence: 99%